2010
DOI: 10.1002/ajim.20825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure of parents to toxic gases in Bhopal on the offspring

Abstract: Exposure of pregnant women to toxic gases in Bhopal in 1984 resulted in high pregnancy loss, increased first 5-year mortality and delayed development of male progeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Results also suggest a post-puberty effect on head circumference of females exposed to gases in utero [57] A high incidence spontaneous abortions and still-births in gas-exposed pregnant women and significantly higher perinatal and neonatal mortalities in the affected areas were reported response of cultured human colon epithelial-FHC cells to methyl isocyanate has been previously investigated with regard to genomic instability in colonocytes [61]. According to Raghuram et al [62], ovarian epithelial cells manifest a persistent DNA damage response upon treatment with methyl isocyanate.…”
Section: In Utero Studies Parameters Studied Referencesmentioning
confidence: 62%
See 2 more Smart Citations
“…Results also suggest a post-puberty effect on head circumference of females exposed to gases in utero [57] A high incidence spontaneous abortions and still-births in gas-exposed pregnant women and significantly higher perinatal and neonatal mortalities in the affected areas were reported response of cultured human colon epithelial-FHC cells to methyl isocyanate has been previously investigated with regard to genomic instability in colonocytes [61]. According to Raghuram et al [62], ovarian epithelial cells manifest a persistent DNA damage response upon treatment with methyl isocyanate.…”
Section: In Utero Studies Parameters Studied Referencesmentioning
confidence: 62%
“…The non-targeted effects of toxic exposure such as bystander responses, genomic instability, gene induction, adaptive responses and low hypersensitivity may also be mirrored as trans-generational health effects. Sarangi et al [57] report that exposure of pregnant workers have demonstrated that exposure to MIC by inhalation results in bone marrow damage, indicating that MIC or its reactive metabolites possess systemic genotoxic/cytotoxic activity [48][49][50]. MIC exposure was found to lead to inhibition of bone marrow cell proliferation by evaluation of the mutagenic and cytotoxic effects of MIC with a mouse micronucleus test [51].…”
Section: Methyl Isocyanate and Cytogenetic Damagementioning
confidence: 99%
See 1 more Smart Citation
“…long-term effects in the BMAP Following exposure to the toxic MIC-gas, many succumbed to death instantly, and those who survived yet suffer from agonizing prolonged health issues. Since then, the long-term effects of the exposed survivors and transgenerational repercussions in their offspring born post-exposure remain contentious [11][12][13] . For the past three decades, the government and non-government organizations have been striving to understand the MIC-induced late effects in the BMAP.…”
Section: What We Know?mentioning
confidence: 99%
“…While there is an uncertainty and debate since 1994 regarding the long-term health effects in the MIC affected population. Increased cancer morbidity , genetic instability (Malla et al, 2011), pregnancy loss and delayed development in male progenies (Sarangi et al, 2010) were recently reported exposure-effects in the MIC affected population after 27 years.…”
mentioning
confidence: 99%